Cybercrime and Digital Awareness: Media Influence and Public Behavior in India Through Structural Equation Modeling (International Journal of Advanced Digital Systems and Multidisciplinary Studies, 2026)
The rapid expansion of digital technologies in India has significantly increased citizens’ exposure to cybercrimes, making digital awareness a critical concern. While technical safeguards continue to evolve, human behavior and perception remain central to effective cybersecurity. This study examines the role of media in shaping public awareness, risk perception, and protective behavior related to cybercrime in the Indian context. Using a structured questionnaire and applying Structural Equation Modeling (SEM), the research analyzes the relationships among media exposure, perceived cyber risk, self-efficacy, digital awareness, and cybersecurity practices. The findings reveal that media plays a significant role in enhancing cybercrime awareness and indirectly influences safe online behavior through perceived risk and self-efficacy. The results highlight that increased awareness alone is insufficient unless accompanied by confidence in one’s ability to respond to cyber threats. This study contributes to existing literature by integrating media influence and behavioral factors into a unified empirical model. The outcomes provide valuable insights for policymakers, educators, and cybersecurity professionals to design more effective awareness campaigns and public education programs aimed at strengthening digital resilience and promoting safer online behavior among citizens in India.